Survey of plant parasitic nematodes and banana weevil on Ensete ventricosum in Ethiopia - Bogale, M.; Speijer, P.R.; Mekete, T.; Mandefro, W.; Tessera, M.; Gold, C. (2004)
Twenty five sites, representative of seven agro-ecological zones of enset (Ensete ventricosum) crops, were sampled between September 1998 and January 1999. At each site, five 1-2 year old enset plants were sampled to check for the presence of nematodes present in their roots. The predominant nematode species found was Pratylenchus goodeyi (prominence value = 5640 per 100 g fresh root weight (FRW)), followed by Aphelenchoides ensete (prominence value = 137 per 100 g FRW), and Meloidogyne spp. (prominence value = 26 per 100 g FRW). Leaves of young enset plants often showed severe streak-like symptoms. Aphelencoides ensete was the only nematode isolated from these leaves and may be associated with the streak-like symptoms. A total of 71 different enset cultivar names were recorded during the survey, with different levels of P. goodeyi. Split pseudostem traps failed to detect the banana weevil, Cosmopolites sordidlus.